2015
DOI: 10.1016/j.jff.2014.07.009
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the total antioxidant capacity and antioxidant compounds of different solvent extracts of Chilgoza pine nuts (Pinus gerardiana)

Abstract: A B S T R A C TThe total antioxidant capacity of Pinus gerardania, or Chilgoza and the presence of antioxidant compounds which typically exist in pine nuts were quantified. Oxygen radical absorbance capacity assay, ferric reducing antioxidant power, and the 2, 2-diphenyl-1-picrylhydrazyl (DPPH•) and 2, 2-azinobis-(3-ethylbenzothiazoline-6-sulfonic acid) (ABTS•+) radical cation scavenging assays were conducted on dichloromethane, ethanol, ethyl acetate, hexane, methanol and water extracts of Chilgoza. The water… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 44 publications
0
32
2
Order By: Relevance
“…In general, the bioactive properties (as antioxidant) of the natural resources, in our case of pine bark, may differ from plant to plant due to a number of environmental factors such as the level of maturity, the growing conditions (location, soil status, climate, and agricultural practices), and also the conditions of storage of postharvest material (temperature, time, humidity, presence of contaminants, etc.). 34 The different methods used for determination of antioxidant activity allows different mechanisms of action of extracts to be evaluated. The FRAP method is based on the reduction of a Fe 3+ complex to Fe 2+ , confirming the presence of reducing antioxidants.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…In general, the bioactive properties (as antioxidant) of the natural resources, in our case of pine bark, may differ from plant to plant due to a number of environmental factors such as the level of maturity, the growing conditions (location, soil status, climate, and agricultural practices), and also the conditions of storage of postharvest material (temperature, time, humidity, presence of contaminants, etc.). 34 The different methods used for determination of antioxidant activity allows different mechanisms of action of extracts to be evaluated. The FRAP method is based on the reduction of a Fe 3+ complex to Fe 2+ , confirming the presence of reducing antioxidants.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…al., 2014, reported approximately 50% fat, 30% protein, 10% carbohydrate, 4% ash and 6% moisture in Pine nuts. 44 The seeds with edible kernels are obtained from ripe cones credited with carminative stimulant and expectorant properties. Analysis of kernels possesses delicate terbinthine flavor, moisture (7.5%), protein (15.9%), fat (49.9%), carbohydrates (21.6%), fibre (2.2), and mineral matter ( 2.9%).…”
Section: Phytochemical Constituentsmentioning
confidence: 99%
“…MP‐AA/W showed the lowest ORAC and PSC (Table ). Whereas water extract of Chilgoza powder exhibited a strong antioxidant activity when compared to pure dichloromethane, ethanol, ethyl acetate, hexane and methanol extract (Hoon et al ., ). These references indicated that change in solvent type and polarity might significantly influence the antioxidant activity of obtained extracts.…”
Section: Resultsmentioning
confidence: 97%